The effective sedative dose of remimazolam for BIS <60 during general anesthesia induction between elderly and non-elderly patients-A randomized controlled trial - Zheng, Jun-Li; Sun, Jie-Feng; Han, Qing; Shi, Si-Ren; Zhou, Jin; Wang, Wei-Long; Huang, Xiao-Dong; Zhou, Zhen-Feng (Frontiers in Pharmacology, 2025)
BackgroundThere is lack research about the effect of sufentanil on the effective dose of remimazolam during general anesthesia in both elderly and non-elderly patients scheduled for day surgery. This study was conducted to estimate the 95% effective dose (ED95) of remimazolam with low dose of sufentanil for BIS <60 during general anesthesia in both elderly and non-elderly patients scheduled for day surgery.MethodsPatients scheduled for elective gynecological day procedures were randomly allocated to one of four dosage groups receiving 0.1, 0.2, 0.3, or 0.4 mg/kg of remimazolam, with 25 participants per group. All patients received a concurrent intravenous dose of sufentanil (0.1 μg/kg) during anesthesia induction. Successful sedation was defined as achieving a BIS score of <60 within 5 minutes of remimazolam administration. The ED50 and ED95 of remimazolam for BIS <60 during general anesthesia induction were calculated. Secondary outcomes included the incidence of hypotension, respiratory depression, and adverse events.ResultsIn elderly patients, the estimated ED50 of remimazolam was determined to be 0.156 mg/kg, with a 95% confidence interval (CI) ranging from 0.110 to 0.190 mg/kg. For non-elderly individuals, the corresponding ED50 was 0.218 mg/kg (95% CI: 0.179–0.253 mg/kg). Additionally, the dose required to achieve 95% efficacy (ED95) was calculated as 0.336 mg/kg (95% CI: 0.286–0.437 mg/kg) in the elderly cohort and 0.418 mg/kg (95% CI: 0.361–0.528 mg/kg) in the non-elderly cohort. Hypotension occurred significantly more often in elderly patients (P < 0.05), but not for the incidence of bradycardia or respiratory depression between groups (P > 0.05).ConclusionUnder BIS monitoring during gynecological day surgery, the estimated ED95 of remimazolam with 0.1 μg/kg sufentanil was 0.336 mg/kg (95% CI: 0.286–0.437 mg/kg) for elderly patients and 0.418 mg/kg (95% CI: 0.361–0.528 mg/kg) for non-elderly patients.Clinical Trial RegistrationThis study is registered with ClinicalTrials.gov as ChiCTR2400091138.